Some observations on glass beads composition in Sarawak, Singapore and Peninsula Malaysia - Zuliskandar Ramli; Nik Hassan Shuhaimi Nik Abd. Rahman; Adnan Jusoh; Yunus Sauman (Universiti Kebangsaan Malaysia, 2011)
Since a great contribution by Beck in 1930’s in studying beads especially in Southeast Asia region, a few other scholars have been encouraged to study the beauty of beads typologically and scientifically. Lamb for example has published several articles on beads in Southeast Asia and other parts of the world. Lamb also analyzed scientifically several beads from Kuala Selinsing,Pengkalan Bujang and Takuapa and demonstrated their compositional data.Tom Harrison, who has done a wonderful job on Sarawak beads also reported in his article, a research on Kuala Selinsing glass beads, Bukit Maras, Santubong associated with Tang and Song ceramics and a Buddha Gupta sculpture and also glass beads worn by Kelabit people. These beads have beenanalyzed scientifically and the result showed that Kuala Selinsing glass beads have a different compositional content with the Santubong glass beads and also Kelabit glass beads. Harrison suggested that glass beads from Kelabit have Chinese origin based on higher lead content in the beads. In this article, we would like to compare the compositional data of Sarawak glass beads with the data taken from Kuala Selinsing, Fort Canning, Singapore and Sungai Mas, Kedah glass beads. The compositional aspect of Santubong, Kelabit, Kuala Selinsing, Sungai Mas and Fort Canning will be analyzed and their differences and similarities will be discussed. According to our research, Bukit Maras, Santubong glass beads have a similar composition of elements with the Sungai Mas, Kedah glass beads and beads worn by Kelabit people are probably not of Chinese origin but have similar content of lead with the glass introduced in Europe in the seventeenth century AD.